Patients 'questions about the conducts of health professionals during hospital intervention (Research, Society and Development, 2021)
The aim of this study is to apprehend patients' doubts about health behaviors performed by different professionals during the hospitalization period. This is a descriptive qualitative study, carried out with 63 patients from a university hospital, who said they had doubts about the treatment performed by the health team during hospitalization. The data were obtained through a recorded telephone interview conducted with the patient or with a family member or caregiver. The results were analyzed and expressed in two categories and four subcategories. The first category, more prevalent, brings uncertainties regarding the treatments or procedures that were performed during hospitalization. The second category considered doubts about non-conclusive medical diagnoses and the lack of consensus among different health professionals. The failure of communication between professional and patient was evidenced in the reports of the subjects of this study. This result reinforces the importance of investments in interpersonal relationships, communication and literacy both in the training of professionals and in the practice of health services.